How Can the Implementation of a Problem Posing Approach Promote Critical Reflection in the English Class? (2016)
ABSTRACT: This action research study intended to explore how problem posing promotes critical reflection through the discussion of social issues in the English class. The project was carried out in a public school in Medellin city. Actions consisted in first connecting class topics to students’ interests and realities, then including two strategies (code switching and true cognates) to ease students’ participation in class discussions, introducing problem posing as a teaching approach, and finally, evaluating the impact of problem posing on students learning process. Data were gathered through surveys to students, interviews to my CT, journals and students’ produced artifacts. Findings revealed that problem posing fostered participation, language development, and critical reflection on the students’ part.